Seriality: Development and disruption in the contemporary medial and cultural environment. (June 2019) - Buonanno, Milly
This article aims to problematise two main tendencies that can be discerned in recent scholarship concerning seriality and how the new era of bountiful production and consumption of serialised narratives relates to seriality as we have known it in previous eras. At stake here are matters of continuity and/or disruption in the changing landscape of media storytelling. I define the two tendencies, respectively, as denied continuity – since it argues for a radical break between contemporary and earlier serial televisual forms – and disregarded disruption – with reference to the apparent blindness of academia with respect to the disruption of seriality brought about by new technology and culturally enabled viewing practices.